Mindfulness training improves attentional task performance in incarcerated youth: a group randomized controlled intervention trial - Leonard, Noelle R.; Jha, Amishi P.; Casarjian, Bethany; Goolsarran, Merissa; Garcia, Cristina; Cleland, Charles M.; Gwadz, Marya V.; Massey, Zohar (Frontiers in Psychology, 2013)
We investigated the impact of cognitive behavioral therapy and mindfulness training (CBT/MT) on attentional task performance in incarcerated adolescents. Attention is a cognitive system necessary for managing cognitive demands and regulating emotions. Yet persistent and intensive demands, such as those experienced during high-stress intervals like incarceration and the events leading to incarceration, may deplete attention resulting in cognitive failures, emotional disturbances, and impulsive behavior. We hypothesized that CBT/MT may mitigate these deleterious effects of high stress and protect against degradation in attention over the high-stress interval of incarceration. Using a group randomized controlled trial design, we randomly assigned dormitories of incarcerated youth, ages 16 to 18, to a CBT/MT intervention (youth n = 147) or an active control intervention (youth n = 117). Both arms received approximately 750 minutes of intervention in a small-group setting over a 3-5 week period. Youth in the CBT/MT arm also logged the amount of out-of-session time spent practicing MT exercises. The Attention Network Test was used to index attentional task performance at baseline and 4 months post-baseline. Overall, task performance degraded over time in all participants. The magnitude of performance degradation was significantly less in the CBT/MT vs. control arm. Further, within the CBT/MT arm, performance degraded over time in those with no outside-of-class practice time, but remained stable over time in those who practiced mindfulness exercises outside of the session meetings. Thus, these findings suggest that sufficient CBT/MT practice may protect against functional attentional impairments associated with high-stress intervals. Keywords: adolescent development, incarcerated adolescents, detained adolescents, stress, attention, mindfulness meditation.